Elimination of waste through value add/non value add process analysis to improve cost productivity in manufacturing - a case study - Kam, Choi Ng; Chee, Peng Lim; Chong, Kuan Eng; Goh, Gerald Guan Gan (2013)
Value Stream Mapping (VSM) is a very comprehensive tool to that allows an organization to identify sources of waste and implements process improvements. This paper describes the adoption of VSM in a semiconductor manufacturing company to improve personnel efficiency and optimize headcount in the production lines. Based on the future state of the value stream mapping a new production process flow was implemented. Non value added activities were reduced or removed by assigning butterfly operators to perform these tasks. The new system successfully resulted in the reduction of six headcounts in the taping process. This is equivalent to a saving of approximately eighty seven thousand Malaysian ringgits per annum. This systematic approach can be similarly employed by the lean practitioners to conduct lean activities in other manufacturing sectors.